(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Recently, the processes of bioconversion of renewable lignocellulosic raw materials into various products (alcohols, organic acids, amino acids, etc.) have reached an industrial scale [1, 2]. The main component of such raw materials is cellulose; its content in the starting material can reach 40–50% and higher [3]. The stage of enzymatic hydrolysis of cellulose to glucose in these processes is the key and most laborious. For the effective hydrolysis of cellulose, it is necessary to have a well-balanced cellulase complex, including endoglucanases (EG) and cellobiohydrolases (CBH), which cleave the polymer substrate to cellobiose and other oligosaccharides, as well as exoglucosidases that catalyze the hydrolysis of oligosaccharides to glucose [4]. Currently, the search for new, more active cellulases remains an urgent task. Intensive research is also underway to increase the specific activity of enzymes and improve their other properties by protein engineering methods [5–7]. To optimize the composition of the cellulase complex, approaches are often used based on the creation of model mixtures of purified enzymes and testing their hydrolytic ability with respect to various cellulose-containing substrates [7–9].